WEB-BASED HALL BOOKING SYSTEM USING ASP.NET - MELISSA, JABLY (Universiti malaysia sarawak (UNIMAS), 2005)
The rapid growth of new technology application in today's world in some way has force all walks of life around the globe to step towards a systematic and efficient manner in all aspect in life. In most of the organizations nowadays, a manual system is no longer in used as most of them are transformed to a computerized system. While companies are competing in altering the existing system to web-based application system, the main reason of this technology approach is often taken for granted. Pertaining to this, not all of web-based application system nowadays is usable as expected. In this project, an online web-based Hall Booking System is developed with the aim to create a usable web application system that can assist user to reserve a hall in an efficient way. A hall recommendation function is one of the user assistance provided in this web-based application system. This online system will act as an interactive medium between user and the hall management in making a hall reservation.